COVID-19 and the Energy Transition - Bassam Fattouh; David Robinson (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2020)
The COVID-19 pandemic may be giving us glimpses of what the future of the energy sector will bring; and the glimpses keep coming as the pandemic continues with no early end in sight. There are two general themes that run through the articles in this Forum, reflecting that we are still in the middle of a global crisis. One is that uncertainty about the longer-term is even greater than usual, because we do not know how governments and consumers are going to behave in a post-COVID world. The other is the tension between short-term imperatives (financial stresses) and the longer-term need for investment and adaptation that is also unusually high. The articles in this issue reflect a wide diversity of views on the effect of COVID-19 on the energy transition, ranging from acceleration of the process to slowing it down, with some arguing that it will have little lasting impact. The professional background of the contributors helps to explain the diversity of views, with articles from different parts of the energy sector, the financial sector, NGOs, and think tanks. Nevertheless, there is a general acceptance that the energy transition was already well underway before COVID-19 and that the recovery programme could well determine the nature and the speed of the transition in different parts of the world and reinforce global trends that were already apparent. Most authors believe that stimulus measures to limit the human and economic impact of the COVID-19 pandemic offer a chance to rebuild a cleaner and more sustainable world, but others are more sceptical. There also seems to be an acceptance that the pace of the energy transition will not be uniform across the globe and that weakened international cooperation reduces the chance of fast-tracking and mainstreaming the low-carbon transition globally.
Keywords: 330